Kadak is a scarf of offering and consecration (from the history of tradition) - Lamazhaa, Chimiza K.; Shaimerdenova, Mendyganym J. (The New Research of Tuva, 2024)
The article analyzes the history of the traditional Tuvan ritual scarf, or “kadak”. Etymological research shows that the name of the scarf is derived from the Tibetan language, and it came into use in Tuvan culture as a result of the influence of both Tibetan Buddhist and non-Buddhist traditions, with significant influence from Mongolian Buddhism. This can be seen in the adoption of practices and rituals from both traditions. The peaceful coexistence of Buddhism and Shamanism in Tuvan society led to the widespread use of kadak scarves by shamans in rituals. Eyewitness accounts from the late 19th and early 20th centuries, as well as subsequent ethnographic research, confirm that kadaks become an integral part of the shamanic tradition in Tuva. Kadaks were not only used in shamanic rituals, but also in Buddhist religious ceremonies. They were often paired with colored chalama ribbons, which were also an important part of shamanic practice. Kodaks were also used in Buddhist religious rituals in Tuva. In addition to their religious significance, the symbolism of the offering, which originated in Tibetan pre-Buddhist culture, was also adopted. This tradition was combined with the Tuvan custom of presenting ribbons made from animal skins. The strong connection between Kodaks and Tuvan culture is evident in the symbols used by the Tuvan People’s Republic, which was restored after the Soviet era. The complex history of ribbons in Tuva shows that the region is part of a larger, diverse culture of ribbons and flags that spans the Eurasian steppes.